Long-term CCNC measurements at the central European ACTRIS research station Melpitz, Germany, 2012-2016 - Yuan Wang; Silvia Henning; Laurent Poulain; Frank Stratmann; Hartmut Herrmann; Alfred Wiedensohler (PANGAEA, 2021)
Atmospheric aerosol measurements were conducted at the Melpitz observatory, Germany. The data was collected during 2012 to 2016, measured by Droplet Measurement Technologies Cloud Condensation Nucleus Counter (DMT-CCNC).
In: Wang, Y et al. (2021): Long-term CCN measurements at the central European ACTRIS research station Melpitz, Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938215